Pengembangan E-Modul IPAS Materi Menjelajahi Bumi dan Antariksa Kelas 6 Di SDN Malasan Wetan 1 - Hasanah, Putri Shofiya Nur; Sriwijayanti, Ribut Prastiwi; Jannah, Faridahtul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This research aims to produce a development product in the form of e-module for IPAS on exploring Earth and space for 6th grade. The research and development of this product is motivated by the lack of technological integration and digitalization in teaching, which impacts students' understanding and engagement in IPAS learning activities. The method used in this research is Research and Development. This research and development utilizes the DDD-E model by Ivers and Barron. The results of the research conducted at SDN Malasan Wetan 1 on 6th-grade students in the second semester for the material on exploring Earth and space showed that the product trial conducted by the researcher on 5 students in the 6th grade obtained a percentage score of 94%. The validation results from the material expert received a score of 80%, and the media expert received a score of 95%, which is at a feasible level. Based on the validation from the 6th-grade teacher as a learning practitioner, a score of 95.8% was obtained, indicating that the results are categorized as feasible and valid. Based on the research and development of the e-module for IPAS on exploring Earth and space for 6th grade at SDN Malasan Wetan 1, it has been validated because the percentage exceeds 80% and can be considered suitable for use as a medium to assist teachers in explaining the material on exploring Earth and space during learning activities with 6th-grade students.